2011
DOI: 10.1105/tpc.111.087007
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of All AGAMOUS Subfamily Members in Rice Reveals Their Roles in Reproductive Organ Identity Determination and Meristem Determinacy

Abstract: Reproductive organ development is one of the most important steps in the life cycle of plants. Studies using core eudicot species like thale cress (Arabidopsis thaliana) and snapdragon (Antirrhinum majus) have shown that MADS domain transcription factors belonging to the AGAMOUS (AG) subfamily regulate the identity of stamens, carpels, and ovules and that they are important for floral meristem determinacy. Here, we investigate the genetic interactions between the four rice (Oryza sativa) AG subfamily members, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
206
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(215 citation statements)
references
References 61 publications
7
206
1
1
Order By: Relevance
“…However, unlike PMADS3, FBP6 is also able to interact with FBP26 (Immink et al, 2003), perhaps indicative of the unique function of FBP6 in style and stigma development or in other processes yet to be uncovered. Recently, it was shown that the rice C-function is also redundantly encoded by its two C-clade genes (Dreni et al, 2011). This contrasts with the situation in Arabidopsis and snapdragon, harboring three and two C-clade genes, respectively, where in both cases a single gene has taken up the role of the classical C-function (Bowman et al, 1989;Yanofsky et al, 1990;Bradley et al, 1993).…”
Section: Discussion the C-function In Petunia Is Redundantly Encoded contrasting
confidence: 39%
See 1 more Smart Citation
“…However, unlike PMADS3, FBP6 is also able to interact with FBP26 (Immink et al, 2003), perhaps indicative of the unique function of FBP6 in style and stigma development or in other processes yet to be uncovered. Recently, it was shown that the rice C-function is also redundantly encoded by its two C-clade genes (Dreni et al, 2011). This contrasts with the situation in Arabidopsis and snapdragon, harboring three and two C-clade genes, respectively, where in both cases a single gene has taken up the role of the classical C-function (Bowman et al, 1989;Yanofsky et al, 1990;Bradley et al, 1993).…”
Section: Discussion the C-function In Petunia Is Redundantly Encoded contrasting
confidence: 39%
“…Likewise, the seed development phenotype in our fbp7 fbp11 mutants and in the weaker cosuppression lines (Colombo et al, 1997) indicates a unique function for the petunia D-clade genes during seed development. Thus, MADS13, the rice ortholog of STK and FBP7/11, seems to be so far the only D-clade gene that is absolutely required for ovule identity (Dreni et al, 2011).…”
Section: The Petunia C-and D-clade Genes Redundantly Specify Ovule Idmentioning
confidence: 99%
“…2D; Yamaguchi et al, 2006;Dreni et al, 2007;Ohmori et al, 2009;Cui et al, 2010). Protein interactions of OsMADS1 with OsMADS13 (a class D gene), OsMADS7, and OsMADS8 (Favaro et al, 2002;Cui et al, 2010) and its genetic interactions with OsMADS6, OsMADS3, OsMADS58, and OsMADS13 (Dreni et al, 2011;Li et al, 2011aLi et al, , 2011bSupplemental Fig. S8) suggest that higher order complexes of these factors may promote meristem termination and ovule development.…”
Section: Interactions Among Mads Factors During Floret Organogenesis mentioning
confidence: 99%
“…In situ hybridization experiments were performed as described previously by Dreni et al (2011) using as probe STK antisense RNA, which corresponds to nucleotides 455 to 818 (Brambilla et al, 2007).…”
Section: Gus Staining and In Situ Hybridizationmentioning
confidence: 99%